Preparation method of semi-solid lithium battery diaphragm
By using semi-solid lithium battery separators composed of polyethylene, polypropylene, foam rubber, phenolic foam plastic and alumina polymer-based materials, the existing separator materials are poorly strong and unable to meet both lightweight and thermal insulation performance, and the lightweight and excellent thermal insulation performance of the separator are achieved.
Patent Information
- Application Number
- CN202411917975.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
The existing lithium battery separator materials have poor strength and cannot meet the needs of lightweight and thermal insulation performance at the same time.
A semi-solid lithium battery separator consisting of polyethylene, polypropylene, foam rubber, phenolic foam plastic and alumina polymer-based materials is prepared by dispersing mechanism, mixed and dried, and finally formed by spray drying.
It realizes the lightweight and excellent thermal insulation performance of the diaphragm, which can meet the requirements of heat insulation and fire protection at the same time, and improves the high temperature resistance and permeability of the diaphragm.
Smart Images

Figure BDA0005207244500000151 
Figure BDA0005207244500000161 
Figure HDA0005207244510000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a method for preparing a semi-solid lithium battery separator. Background Art
[0002] In the structure of semi-solid lithium batteries, the composite diaphragm is one of the key inner components. The performance of the composite diaphragm determines the interface structure, internal resistance, etc. of the semi-solid lithium battery, and directly affects the capacity, cycle and safety performance of the semi-solid lithium battery. Composite diaphragms with excellent performance play an important role in improving the comprehensive performance of semi-solid lithium batteries.
[0003] The Chinese patent with announcement number CN113764820B discloses a method for preparing a composite high-temperature resistant lithium battery separator material, comprising the following steps: Step 1, preparing a coating slurry: adding powder, active agent and adhesive to deionized water in sequence, stirring thoroughly to obtain a coating slurry; Step 2, base film coating: the base film is sequentially cleaned, dried and flattened, and then plasma treated, and then the coating slurry is applied to the surface of the base film through a sprayer to form a preliminary coating of the base film; Step 3, base film post-treatment: the preliminary coating of the base film is sequentially dried, shaped and rolled to obtain a composite high-temperature resistant lithium battery separator material. The preparation process of this patent is to first plasma treat the base film and then apply the high-temperature resistant slurry to the surface of the base film, and then dry, shape and roll it to obtain a composite high-temperature resistant lithium battery separator material. The preparation method is simple and easy to operate, and the prepared battery separator also has better high temperature resistance and good permeability.
[0004] In actual use, the lithium battery separator of the above patent has poor strength of the separator material and cannot meet the requirements of both lightweight and heat insulation performance; therefore, it does not meet existing needs. In this regard, we propose a method for preparing a semi-solid lithium battery separator. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a semi-solid lithium battery separator, which solves the problem that the lithium battery separator mentioned in the above background technology has poor strength of the separator material during actual use and cannot meet the requirements of lightweight and heat insulation performance at the same time.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a semi-solid lithium battery separator, wherein the semi-solid lithium battery separator is composed of polyethylene, polypropylene, foamed rubber, phenolic foam plastic and alumina polymer-based materials, and the method for preparing the semi-solid lithium battery separator comprises the following steps:
[0007] S1: Prepare polyethylene, polypropylene, foam rubber, phenolic foam plastic, alumina polymer-based materials, and screen miscellaneous materials;
[0008] S2: preparing polyethylene, polypropylene, foam rubber and phenolic foam plastic into nano oxide powders respectively by a disperser;
[0009] S3: mixing polyethylene nano oxide powder, polypropylene nano oxide powder, foam rubber nano oxide powder, phenolic foam plastic nano oxide powder and alumina polymer-based material;
[0010] S4: drying the mixture;
[0011] S5: Check the performance of the diaphragm.
[0012] Preferably, in S1, the semi-solid lithium battery separator comprises the following raw materials in parts by mass:
[0013] 15-20 parts of polyethylene, 10-15 parts of polypropylene, 10-15 parts of foamed rubber, 5-10 parts of phenolic foam plastics, and 15-20 parts of alumina polymer-based materials.
[0014] Preferably, in said S1, screening the base material and miscellaneous materials comprises the following steps:
[0015] S1-1: Extract and dry polyethylene, polypropylene, foam rubber, phenolic foam plastics, and alumina polymer-based materials and place them in a filter tray;
[0016] S1-2: Install a vibration plate outside the filter plate, and drive the filter plate to vibrate through the vibration plate, drive the dry base material to shake, so that the dust on the surface of the base material is shaken off;
[0017] S1-3: Clean the vibration plate and filter plate, and perform secondary cleaning on the base material;
[0018] S1-4: After classification and cleaning, seal and store.
[0019] Preferably, in S2, the powder making method of the disperser comprises the following steps:
[0020] S2-1: Place polyethylene, polypropylene, foam rubber, phenolic foam plastic, and alumina polymer-based materials into a grinding disc respectively;
[0021] S2-2: Place the grinding disc on the grinder, drive the grinding disc to rotate counterclockwise through grinding, and then apply pressure to the surface of the grinding disc through the pressure roller, so that the base material and the grinding disc rotate and rub against each other to form nano oxide powders.
[0022] Preferably, in S3, mixing nano oxide powders comprises the following steps:
[0023] S3-1: dissolving a calculated amount of foamed rubber in deionized water, transferring the mixture to a vacuum reactor, then adding a calculated amount of polyethylene and polypropylene, and reacting the mixture in an oil bath at 150°C to 200°C for 12h to 24h, followed by cooling, centrifugation, washing, and precipitation to obtain a high-concentration rubber slurry;
[0024] S3-2: The high-concentration rubber slurry prepared in S1 and deionized water are mixed and stirred in a vacuum reactor for 30 minutes to 2 hours to prepare a concentrated rubber slurry at a temperature of 60°C to 80°C;
[0025] S3-3: Add the calculated amount of phenolic foam plastic powder, alumina polymer powder and an appropriate amount of cross-linking agent into a vacuum reactor, then move to a vacuum reactor at 80°C to 120°C and stir for 30 minutes to 2 hours to dissolve, and mix to obtain a diaphragm solution.
[0026] Preferably, the crosslinking agent is a polymer mixed with divinylbenzene, diisocyanate and N,N-methylenebisacrylamide. The crosslinking agent polymerizes the powder and the rubber slurry to a certain extent to cause crosslinking, so that the product becomes an insoluble crosslinked polymer.
[0027] Preferably, in S4, the drying of the mixture comprises the following steps:
[0028] S4-1: Apply the membrane solution prepared in S3 onto the substrate, let it stand in a vacuum until a film is formed, and then peel it off and dry it;
[0029] S4-2: The peeled film is worked by spray drying;
[0030] S4-3: During the drying process, the coating slurry solidifies on the surface of the semi-solid lithium battery separator to form a semi-solid lithium battery separator.
[0031] Preferably, in S5, the diaphragm detection work includes the following steps:
[0032] S5-1: Use a sampler to cut 5 samples from the surface of the semi-solid lithium battery separator to be tested;
[0033] S5-2: Set the test speed, sample name, test times and other parameter information on the intelligent electronic tensile testing machine control software;
[0034] S5-3: Clamp the sample in a special fixture and install the puncture needle;
[0035] S5-4: The test starts, and the puncture needle moves to puncture the sample at the set test speed. The equipment displays the force value changes in real time and reports the puncture force value at the end of the test.
[0036] Preferably, the foamed rubber includes a foaming agent, and the foaming agent is at least one of calcium carbonate, magnesium carbonate and sodium bicarbonate.
[0037] Preferably, the phenolic foam is prepared by treating polystyrene resin polymerized into beads with pentane under heating and pressure to obtain so-called expandable polystyrene beads.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The present invention adds foamed rubber and phenolic foam plastics into the base material and adopts phenolic foam plastics as the semi-solid lithium battery diaphragm insulation material, which can meet the requirements of thermal insulation and fire prevention at the same time. The phenolic foam plastics are used as a material for sealing and controlling fire in semi-solid lithium batteries, which can fundamentally prevent the double safety and health hazards brought to people by the dust and fine fiber pollution of organic flammable materials and inorganic materials. In addition to being lightweight, the foamed rubber and plastic material also has excellent thermal insulation performance. The tiny bubbles inside it can effectively prevent the conduction and loss of heat, so that the material has good thermal insulation effect.
[0040] 2. The present invention adds a cross-linking agent. The function of the cross-linking agent is to generate chemical bonds between linear molecules, so that the linear molecules are connected to each other to form a network structure, thereby improving the strength and elasticity of the rubber. The cross-linking agent used in the rubber is mainly sulfur. In addition, a promoter is added to transform the linear or slightly branched macromolecules into a three-dimensional network structure, thereby improving the strength, heat resistance, wear resistance, solvent resistance and other properties, and improving the foaming effect. Through spray drying, the solution and emulsion can be directly dried into a powder or granular product, which can omit the processes of evaporation and crushing. The preparation method is simple and easy to operate, and the prepared battery separator also has better high temperature resistance and good permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In order to solve the problem that the existing lithium battery separators have poor strength in actual use and cannot meet the requirements of both lightweight and heat insulation performance, please refer to Figure 1 , this embodiment provides the following technical solutions:
[0044] Embodiment 1:
[0045] A method for preparing a semi-solid lithium battery separator, wherein the semi-solid lithium battery separator is composed of polyethylene, polypropylene, foamed rubber, phenolic foam plastic and alumina polymer-based materials, and the method for preparing the semi-solid lithium battery separator comprises the following steps:
[0046] S1: Prepare polyethylene, polypropylene, foam rubber, phenolic foam plastic, alumina polymer-based materials, and screen miscellaneous materials;
[0047] S2: preparing polyethylene, polypropylene, foam rubber and phenolic foam plastic into nano oxide powders respectively by a disperser;
[0048] S3: mixing polyethylene nano oxide powder, polypropylene nano oxide powder, foam rubber nano oxide powder, phenolic foam plastic nano oxide powder and alumina polymer-based material;
[0049] S4: drying the mixture;
[0050] S5: Check the performance of the diaphragm.
[0051] It should be noted that the preparation method is simple and easy to operate, and the prepared battery separator also has better high temperature resistance and good permeability.
[0052] The semi-solid lithium battery separator includes the following raw materials by weight:
[0053] Polyethylene 15 parts
[0054] Polypropylene 10 parts
[0055] Foam rubber 10 parts
[0056] 5 parts of phenolic foam
[0057] 15 parts of alumina polymer-based material.
[0058] Screening of base material miscellaneous materials includes the following steps:
[0059] S1-1: Extract and dry polyethylene, polypropylene, foam rubber, phenolic foam plastics, and alumina polymer-based materials and place them in a filter tray;
[0060] S1-2: Install a vibration plate outside the filter plate, and drive the filter plate to vibrate through the vibration plate, drive the dry base material to shake, so that the dust on the surface of the base material is shaken off;
[0061] S1-3: Clean the vibration plate and filter plate, and perform secondary cleaning on the base material;
[0062] S1-4: After classification and cleaning, seal and store.
[0063] The powder making method of the disperser comprises the following steps:
[0064] S2-1: Place polyethylene, polypropylene, foam rubber, phenolic foam plastic, and alumina polymer-based materials into a grinding disc respectively;
[0065] S2-2: Place the grinding disc on the grinder, drive the grinding disc to rotate counterclockwise through grinding, and then apply pressure to the surface of the grinding disc through the pressure roller, so that the base material and the grinding disc rotate and rub against each other to form nano oxide powders.
[0066] Mixing nano oxide powders, comprising the following steps:
[0067] S3-1: dissolving a calculated amount of foamed rubber in deionized water, transferring the mixture to a vacuum reactor, then adding a calculated amount of polyethylene and polypropylene, and reacting the mixture in an oil bath at 150°C to 200°C for 12h to 24h, followed by cooling, centrifugation, washing, and precipitation to obtain a high-concentration rubber slurry;
[0068] S3-2: The high-concentration rubber slurry prepared in S1 and deionized water are mixed and stirred in a vacuum reactor for 30 minutes to 2 hours to prepare a concentrated rubber slurry at a temperature of 60°C to 80°C;
[0069] S3-3: Add the calculated amount of phenolic foam plastic powder, alumina polymer powder and an appropriate amount of cross-linking agent into a vacuum reactor, then move to a vacuum reactor at 80°C to 120°C and stir for 30 minutes to 2 hours to dissolve, and mix to obtain a diaphragm solution.
[0070] The crosslinking agent is a polymer mixed with divinylbenzene, diisocyanate and N,N-methylenebisacrylamide. The crosslinking agent polymerizes the powder and the rubber slurry to a certain extent to cause crosslinking, so that the product becomes an insoluble crosslinked polymer.
[0071] It should be noted that the role of the cross-linking agent is to produce chemical bonds between linear molecules, so that the linear molecules are connected to each other to form a network structure, thereby improving the strength and elasticity of the rubber. The cross-linking agent used in rubber is mainly sulfur. In addition, an accelerator is added to transform linear or lightly branched macromolecules into a three-dimensional network structure, thereby improving strength, heat resistance, wear resistance, solvent resistance and other properties, and improving the foaming effect.
[0072] The drying process of the mixture includes the following steps:
[0073] S4-1: Apply the membrane solution prepared in S3 onto the substrate, let it stand in a vacuum until a film is formed, and then peel it off and dry it;
[0074] S4-2: The peeled film is worked by spray drying.
[0075] It should be noted that the solution and emulsion can be directly dried into powder or granular products, which can omit the evaporation and crushing processes;
[0076] S4-3: During the drying process, the coating slurry solidifies on the surface of the semi-solid lithium battery separator to form a semi-solid lithium battery separator.
[0077] Diaphragm testing work includes the following steps:
[0078] S5-1: Use a sampler to cut 5 samples from the surface of the semi-solid lithium battery separator to be tested;
[0079] S5-2: Set the test speed, sample name, test times and other parameter information on the intelligent electronic tensile testing machine control software;
[0080] S5-3: Clamp the sample in a special fixture and install the puncture needle;
[0081] S5-4: At the beginning of the test, the puncture needle moves at the set test speed to puncture the sample. The equipment displays the force value changes in real time and reports the puncture force value at the end of the test. The puncture resistance is an important mechanical index for evaluating the performance of diaphragm materials, and can effectively reflect whether the diaphragm is prone to short circuit during assembly.
[0082] The foamed rubber includes a foaming agent, and the foaming agent is at least one of calcium carbonate, magnesium carbonate and sodium bicarbonate.
[0083] It should be noted that in addition to being lightweight, foamed rubber and plastic materials also have excellent thermal insulation properties. The tiny bubbles inside them can effectively prevent the conduction and loss of heat, making the material have good thermal insulation effects.
[0084] The phenolic foam is prepared by treating polystyrene resin polymerized into beads with pentane under heat and pressure to obtain so-called expandable polystyrene beads.
[0085] It should be noted that the use of phenolic foam plastic as a semi-solid lithium battery diaphragm insulation material can meet the requirements of thermal insulation and fire prevention at the same time. As a material for sealing and controlling fire in semi-solid lithium batteries, it can fundamentally eliminate the dual safety and health hazards caused by dust and fine fiber pollution from organic flammable materials and inorganic materials.
[0086] Embodiment 2:
[0087] A method for preparing a semi-solid lithium battery separator, wherein the semi-solid lithium battery separator is composed of polyethylene, polypropylene, foamed rubber, phenolic foam plastic and alumina polymer-based materials, and the method for preparing the semi-solid lithium battery separator comprises the following steps:
[0088] S1: Prepare polyethylene, polypropylene, foam rubber, phenolic foam plastic, alumina polymer-based materials, and screen miscellaneous materials;
[0089] S2: preparing polyethylene, polypropylene, foam rubber and phenolic foam plastic into nano oxide powders respectively by a disperser;
[0090] S3: mixing polyethylene nano oxide powder, polypropylene nano oxide powder, foam rubber nano oxide powder, phenolic foam plastic nano oxide powder and alumina polymer-based material;
[0091] S4: drying the mixture;
[0092] S5: Check the performance of the diaphragm.
[0093] The semi-solid lithium battery separator includes the following raw materials by weight:
[0094] Polyethylene 20 parts
[0095] Polypropylene 15 parts
[0096] Foam rubber 15 parts
[0097] 10 parts of phenolic foam
[0098] 20 parts of alumina polymer-based material.
[0099] Screening of base material miscellaneous materials includes the following steps:
[0100] S1-1: Extract and dry polyethylene, polypropylene, foam rubber, phenolic foam plastics, and alumina polymer-based materials and place them in a filter tray;
[0101] S1-2: Install a vibration plate outside the filter plate, and drive the filter plate to vibrate through the vibration plate, drive the dry base material to shake, so that the dust on the surface of the base material is shaken off;
[0102] S1-3: Clean the vibration plate and filter plate, and perform secondary cleaning on the base material;
[0103] S1-4: After classification and cleaning, seal and store.
[0104] The powder making method of the disperser comprises the following steps:
[0105] S2-1: Place polyethylene, polypropylene, foam rubber, phenolic foam plastic, and alumina polymer-based materials into a grinding disc respectively;
[0106] S2-2: Place the grinding disc on the grinder, drive the grinding disc to rotate counterclockwise through grinding, and then apply pressure to the surface of the grinding disc through the pressure roller, so that the base material and the grinding disc rotate and rub against each other to form nano oxide powders.
[0107] Mixing nano oxide powders, comprising the following steps:
[0108] S3-1: dissolving a calculated amount of foamed rubber in deionized water, transferring the mixture to a vacuum reactor, then adding a calculated amount of polyethylene and polypropylene, and reacting the mixture in an oil bath at 150°C to 200°C for 12h to 24h, followed by cooling, centrifugation, washing, and precipitation to obtain a high-concentration rubber slurry;
[0109] S3-2: The high-concentration rubber slurry prepared in S1 and deionized water are mixed and stirred in a vacuum reactor for 30 minutes to 2 hours to prepare a concentrated rubber slurry at a temperature of 60°C to 80°C;
[0110] S3-3: Add the calculated amount of phenolic foam plastic powder, alumina polymer powder and an appropriate amount of cross-linking agent into a vacuum reactor, then move to a vacuum reactor at 80°C to 120°C and stir for 30 minutes to 2 hours to dissolve, and mix to obtain a diaphragm solution.
[0111] Embodiment 3:
[0112] A method for preparing a semi-solid lithium battery separator, wherein the semi-solid lithium battery separator is composed of polyethylene, polypropylene, foamed rubber, phenolic foam plastic and alumina polymer-based materials, and the method for preparing the semi-solid lithium battery separator comprises the following steps:
[0113] S1: Prepare polyethylene, polypropylene, foam rubber, phenolic foam plastic, alumina polymer-based materials, and screen miscellaneous materials;
[0114] S2: preparing polyethylene, polypropylene, foam rubber and phenolic foam plastic into nano oxide powders respectively by a disperser;
[0115] S3: mixing polyethylene nano oxide powder, polypropylene nano oxide powder, foam rubber nano oxide powder, phenolic foam plastic nano oxide powder and alumina polymer-based material;
[0116] S4: drying the mixture;
[0117] S5: Check the performance of the diaphragm.
[0118] The semi-solid lithium battery separator includes the following raw materials by weight:
[0119] Polyethylene 20 parts
[0120] Polypropylene 15 parts
[0121] Foam rubber 15 parts
[0122] 20 parts of alumina polymer-based material.
[0123] Screening of base material miscellaneous materials includes the following steps:
[0124] S1-1: extract and dry the polyethylene, polypropylene, foam rubber, and alumina polymer-based materials and place them in a filter tray;
[0125] S1-2: Install a vibration plate outside the filter plate, and drive the filter plate to vibrate through the vibration plate, drive the dry base material to shake, so that the dust on the surface of the base material is shaken off;
[0126] S1-3: Clean the vibration plate and filter plate, and perform secondary cleaning on the base material;
[0127] S1-4: After classification and cleaning, seal and store.
[0128] The powder making method of the disperser comprises the following steps:
[0129] S2-1: Place polyethylene, polypropylene, foam rubber, and alumina polymer-based materials into grinding discs respectively;
[0130] S2-2: Place the grinding disc on the grinder, drive the grinding disc to rotate counterclockwise through grinding, and then apply pressure to the surface of the grinding disc through the pressure roller, so that the base material and the grinding disc rotate and rub against each other to form nano oxide powders.
[0131] Mixing nano oxide powders, comprising the following steps:
[0132] S3-1: dissolving a calculated amount of foamed rubber in deionized water, transferring the mixture to a vacuum reactor, then adding a calculated amount of polyethylene and polypropylene, and reacting the mixture in an oil bath at 150°C to 200°C for 12h to 24h, followed by cooling, centrifugation, washing, and precipitation to obtain a high-concentration rubber slurry;
[0133] S3-2: The high-concentration rubber slurry prepared in S1 and deionized water are mixed and stirred in a vacuum reactor for 30 minutes to 2 hours to prepare a concentrated rubber slurry at a temperature of 60°C to 80°C;
[0134] S3-3: Add the calculated amount of alumina polymer powder and an appropriate amount of cross-linking agent into a vacuum reactor, then move to a vacuum reactor at 80°C to 120°C and stir for 30 minutes to 2 hours to dissolve, and mix to obtain a diaphragm solution.
[0135] Embodiment 4:
[0136] A method for preparing a semi-solid lithium battery separator, wherein the semi-solid lithium battery separator is composed of polyethylene, polypropylene, foamed rubber, phenolic foam plastic and alumina polymer-based materials, and the method for preparing the semi-solid lithium battery separator comprises the following steps:
[0137] S1: Prepare polyethylene, polypropylene, foam rubber, phenolic foam plastic, alumina polymer-based materials, and screen miscellaneous materials;
[0138] S2: preparing polyethylene, polypropylene, foam rubber and phenolic foam plastic into nano oxide powders respectively by a disperser;
[0139] S3: mixing polyethylene nano oxide powder, polypropylene nano oxide powder, foam rubber nano oxide powder, phenolic foam plastic nano oxide powder and alumina polymer-based material;
[0140] S4: drying the mixture;
[0141] S5: Check the performance of the diaphragm.
[0142] The semi-solid lithium battery separator includes the following raw materials by weight:
[0143] Polyethylene 15 parts
[0144] Polypropylene 10 parts
[0145] 5 parts of phenolic foam
[0146] 15 parts of alumina polymer-based material.
[0147] Screening of base material miscellaneous materials includes the following steps:
[0148] S1-1: Extract and dry polyethylene, polypropylene, phenolic foam, and alumina polymer-based materials and place them in a filter tray;
[0149] S1-2: Install a vibration plate outside the filter plate, and drive the filter plate to vibrate through the vibration plate, drive the dry base material to shake, so that the dust on the surface of the base material is shaken off;
[0150] S1-3: Clean the vibration plate and filter plate, and perform secondary cleaning on the base material;
[0151] S1-4: After classification and cleaning, seal and store.
[0152] The powder making method of the disperser comprises the following steps:
[0153] S2-1: Place polyethylene, polypropylene, phenolic foam, and alumina polymer-based materials into grinding discs respectively;
[0154] S2-2: Place the grinding disc on the grinder, drive the grinding disc to rotate counterclockwise through grinding, and then apply pressure to the surface of the grinding disc through the pressure roller, so that the base material and the grinding disc rotate and rub against each other to form nano oxide powders.
[0155] Mixing nano oxide powders, comprising the following steps:
[0156] S3-1: adding calculated amounts of polyethylene and polypropylene, and reacting in an oil bath at 150°C to 200°C for 12h to 24h, followed by cooling, centrifugation, washing, and precipitation to obtain a high-concentration rubber slurry;
[0157] S3-2: The high-concentration rubber slurry prepared in S1 and deionized water are mixed and stirred in a vacuum reactor for 30 minutes to 2 hours to prepare a concentrated rubber slurry at a temperature of 60°C to 80°C;
[0158] S3-3: Add the calculated amount of phenolic foam plastic powder, alumina polymer powder and an appropriate amount of cross-linking agent into a vacuum reactor, then move to a vacuum reactor at 80°C to 120°C and stir for 30 minutes to 2 hours to dissolve, and mix to obtain a diaphragm solution.
[0159] Comparative Example 1:
[0160] Compared with Example 1, the difference of Comparative Example 1 is that the above-mentioned phenolic foam plastic and foamed plastic are not added to the semi-solid lithium battery separator.
[0161] A method for preparing a semi-solid lithium battery separator, wherein the semi-solid lithium battery separator is composed of polyethylene, polypropylene and aluminum oxide polymer-based materials, and the method for preparing the semi-solid lithium battery separator comprises the following steps:
[0162] S1: Prepare polyethylene, polypropylene, foam rubber, phenolic foam plastic, alumina polymer-based materials, and screen miscellaneous materials;
[0163] S2: preparing polyethylene and polypropylene into nano oxide powders respectively by a disperser;
[0164] S3: mixing polyethylene nano oxide powder, polypropylene nano oxide powder and alumina polymer-based material;
[0165] S4: drying the mixture;
[0166] S5: Check the performance of the diaphragm.
[0167] The semi-solid lithium battery separator includes the following raw materials by weight:
[0168] Polyethylene 20 parts
[0169] Polypropylene 15 parts
[0170] 20 parts of alumina polymer-based material.
[0171] Screening of base material miscellaneous materials includes the following steps:
[0172] S1-1: After extracting and drying the polyethylene, polypropylene and alumina polymer-based materials, place them in a filter tray;
[0173] S1-2: Install a vibration plate outside the filter plate, and drive the filter plate to vibrate through the vibration plate, drive the dry base material to shake, so that the dust on the surface of the base material is shaken off;
[0174] S1-3: Clean the vibration plate and filter plate, and perform secondary cleaning on the base material;
[0175] S1-4: After classification and cleaning, seal and store.
[0176] The powder making method of the disperser comprises the following steps:
[0177] S2-1: Place polyethylene, polypropylene, and alumina polymer-based materials into grinding discs respectively;
[0178] S2-2: Place the grinding disc on the grinder, drive the grinding disc to rotate counterclockwise through grinding, and then apply pressure to the surface of the grinding disc through the pressure roller, so that the base material and the grinding disc rotate and rub against each other to form nano oxide powders.
[0179] Mixing nano oxide powders, comprising the following steps:
[0180] S3-1: adding calculated amounts of polyethylene and polypropylene, and reacting in an oil bath at 150°C to 200°C for 12h to 24h, followed by cooling, centrifugation, washing, and precipitation to obtain a high-concentration rubber slurry;
[0181] S3-2: The high-concentration rubber slurry prepared in S1 and deionized water are mixed and stirred in a vacuum reactor for 30 minutes to 2 hours to prepare a concentrated rubber slurry at a temperature of 60°C to 80°C;
[0182] S3-3: Add the calculated amount of alumina polymer powder and an appropriate amount of cross-linking agent into a vacuum reactor, then move to a vacuum reactor at 80°C to 120°C and stir for 30 minutes to 2 hours to dissolve, and mix to obtain a diaphragm solution.
[0183] Comparative Example 2:
[0184] Compared with Example 2, the difference of Comparative Example 2 is that the above-mentioned phenolic foam plastic and foamed plastic are not added to the semi-solid lithium battery separator.
[0185] A method for preparing a semi-solid lithium battery separator, wherein the semi-solid lithium battery separator is composed of polyethylene, polypropylene and aluminum oxide polymer-based materials, and the method for preparing the semi-solid lithium battery separator comprises the following steps:
[0186] S1: Prepare polyethylene, polypropylene, foam rubber, phenolic foam plastic, alumina polymer-based materials, and screen miscellaneous materials;
[0187] S2: preparing polyethylene and polypropylene into nano oxide powders respectively by a disperser;
[0188] S3: mixing polyethylene nano oxide powder, polypropylene nano oxide powder and alumina polymer-based material;
[0189] S4: drying the mixture;
[0190] S5: Check the performance of the diaphragm.
[0191] The semi-solid lithium battery separator includes the following raw materials by weight:
[0192] Polyethylene 15 parts
[0193] Polypropylene 10 parts
[0194] 15 parts of alumina polymer-based material.
[0195] Screening of base material miscellaneous materials includes the following steps:
[0196] S1-1: After extracting and drying the polyethylene, polypropylene and alumina polymer-based materials, place them in a filter tray;
[0197] S1-2: Install a vibration plate outside the filter plate, and drive the filter plate to vibrate through the vibration plate, drive the dry base material to shake, so that the dust on the surface of the base material is shaken off;
[0198] S1-3: Clean the vibration plate and filter plate, and perform secondary cleaning on the base material;
[0199] S1-4: After classification and cleaning, seal and store.
[0200] The powder making method of the disperser comprises the following steps:
[0201] S2-1: Place polyethylene, polypropylene, and alumina polymer-based materials into grinding discs respectively;
[0202] S2-2: Place the grinding disc on the grinder, drive the grinding disc to rotate counterclockwise through grinding, and then apply pressure to the surface of the grinding disc through the pressure roller, so that the base material and the grinding disc rotate and rub against each other to form nano oxide powders.
[0203] Mixing nano oxide powders, comprising the following steps:
[0204] S3-1: adding calculated amounts of polyethylene and polypropylene, and reacting in an oil bath at 150°C to 200°C for 12h to 24h, followed by cooling, centrifugation, washing, and precipitation to obtain a high-concentration rubber slurry;
[0205] S3-2: The high-concentration rubber slurry prepared in S1 and deionized water are mixed and stirred in a vacuum reactor for 30 minutes to 2 hours to prepare a concentrated rubber slurry at a temperature of 60°C to 80°C;
[0206] S3-3: Add the calculated amount of alumina polymer powder and an appropriate amount of cross-linking agent into a vacuum reactor, then move to a vacuum reactor at 80°C to 120°C and stir for 30 minutes to 2 hours to dissolve, and mix to obtain a diaphragm solution.
[0207] The following test data were obtained:
[0208]
[0209]
[0210] It can be concluded from the above table that although different proportions of materials are used to prepare the semi-solid lithium battery separators in Example 1 and Example 2, the performance of the prepared semi-solid lithium battery separators is not much different. After heat shrinkage and puncture resistance tests, compared with Comparative Examples 1 and 2 which lack phenolic foam plastics and foamed plastics, it is shown that the semi-solid lithium battery separator prepared by the present invention has stronger heat insulation and puncture resistance.
[0211] Working principle: After polyethylene, polypropylene, foam rubber, phenolic foam plastic, and alumina polymer-based materials are extracted and dried, they are placed in a filter plate; a vibration plate is installed outside the filter plate, and the filter plate is driven to vibrate through the vibration plate, which drives the dry base material to shake, so that the dust on the surface of the base material is shaken off; the vibration plate and the filter plate are cleaned, and the base material is cleaned twice; after the classification and cleaning are completed, they are sealed and stored, polyethylene, polypropylene, foam rubber, phenolic foam plastic, and alumina polymer-based materials are respectively placed in grinding plates, and the grinding plates are placed on the grinder. The grinding plates are driven to rotate counterclockwise through grinding, and then the surface of the grinding plates is pressed by the grinding roller. The base material and the grinding plate are subjected to relative rotation friction to form nano oxide powders, respectively, and the calculated amount of foam rubber is dissolved in deionized water and transferred to a vacuum reactor, and then the calculated amount of polyethylene and polypropylene are added, and the reaction is carried out in an oil bath at 150°C to 200°C for 12h to 24h, and then high-concentration rubber slurry is obtained by cooling, centrifugation, washing, and precipitation. The obtained high-concentration rubber The slurry and deionized water are mixed and stirred in a vacuum reactor for 30min to 2h to obtain a concentrated rubber slurry at a temperature of 60℃ to 80℃. The calculated amount of phenolic foam plastic powder, alumina polymer powder and an appropriate amount of cross-linking agent are added to the vacuum reactor, and then moved to a vacuum reactor at 80℃ to 120°C and stirred for 30min to 2h to dissolve, and the diaphragm solution is obtained by mixing. The prepared diaphragm solution is coated on the substrate, and allowed to stand in a vacuum until a film is formed, and then peeled off and dried. The peeled film is spray dried. During the drying process, the coated slurry is solidified on the surface of the semi-solid lithium battery diaphragm to form a semi-solid lithium battery diaphragm. Five samples are cut from the surface of the semi-solid lithium battery diaphragm to be tested with a sampler. The test speed, sample name, test number and other parameter information are set on the control software of the intelligent electronic tensile testing machine. The sample is clamped in a special fixture and the puncture needle is installed. At the beginning of the test, the puncture needle moves to puncture the sample according to the set test speed, and the equipment displays the force value change in real time, and reports the puncture force value at the end of the test.
[0212] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0213] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing a semi-solid lithium battery separator, characterized in that: The semi-solid lithium battery separator is composed of polyethylene, polypropylene, foamed rubber, phenolic foam plastic and alumina polymer-based materials. The preparation method of the semi-solid lithium battery separator comprises the following steps: S1: Prepare polyethylene, polypropylene, foam rubber, phenolic foam plastic, alumina polymer-based materials, and screen miscellaneous materials; S2: preparing polyethylene, polypropylene, foam rubber and phenolic foam plastic into nano oxide powders respectively by a disperser; S3: mixing polyethylene nano oxide powder, polypropylene nano oxide powder, foam rubber nano oxide powder, phenolic foam plastic nano oxide powder and alumina polymer-based material; S4: drying the mixture; S5: Check the performance of the diaphragm.
2. The method for preparing a semi-solid lithium battery separator according to claim 1, characterized in that: In S1, the semi-solid lithium battery separator includes the following raw materials in parts by mass: 15-20 parts of polyethylene, 10-15 parts of polypropylene, 10-15 parts of foamed rubber, 5-10 parts of phenolic foam plastics, and 15-20 parts of alumina polymer-based materials.
3. The method for preparing a semi-solid lithium battery separator according to claim 2, characterized in that: In S1, screening the base material and miscellaneous materials includes the following steps: S1-1: Extract and dry polyethylene, polypropylene, foam rubber, phenolic foam plastics, and alumina polymer-based materials and place them in a filter tray; S1-2: Install a vibration plate outside the filter plate, and drive the filter plate to vibrate through the vibration plate, drive the dry base material to shake, so that the dust on the surface of the base material is shaken off; S1-3: Clean the vibration plate and filter plate, and perform secondary cleaning on the base material; S1-4: After classification and cleaning, seal and store.
4. The method for preparing a semi-solid lithium battery separator according to claim 1, characterized in that: In S2, the powder making method of the disperser comprises the following steps: S2-1: Place polyethylene, polypropylene, foam rubber, phenolic foam plastic, and alumina polymer-based materials into a grinding disc respectively; S2-2: Place the grinding disc on the grinder, drive the grinding disc to rotate counterclockwise through grinding, and then apply pressure to the surface of the grinding disc through the pressure roller, so that the base material and the grinding disc rotate and rub against each other to form nano oxide powders.
5. The method for preparing a semi-solid lithium battery separator according to claim 1, characterized in that: In S3, mixing nano oxide powders comprises the following steps: S3-1: dissolving a calculated amount of foamed rubber in deionized water, transferring the mixture to a vacuum reactor, then adding a calculated amount of polyethylene and polypropylene, and reacting the mixture in an oil bath at 150°C to 200°C for 12h to 24h, followed by cooling, centrifugation, washing, and precipitation to obtain a high-concentration rubber slurry; S3-2: The high-concentration rubber slurry prepared in S1 and deionized water are mixed and stirred in a vacuum reactor for 30 minutes to 2 hours to prepare a concentrated rubber slurry at a temperature of 60°C to 80°C; S3-3: Add the calculated amount of phenolic foam plastic powder, alumina polymer powder and an appropriate amount of cross-linking agent into a vacuum reactor, then move to a vacuum reactor at 80°C to 120°C and stir for 30 minutes to 2 hours to dissolve, and mix to obtain a diaphragm solution.
6. The method for preparing a semi-solid lithium battery separator according to claim 5, characterized in that: The crosslinking agent is a polymer mixed with divinylbenzene, diisocyanate and N,N-methylenebisacrylamide. The crosslinking agent polymerizes the powder and the rubber slurry to a certain extent to cause crosslinking, so that the product becomes an insoluble crosslinked polymer.
7. The method for preparing a semi-solid lithium battery separator according to claim 1, characterized in that: In S4, the drying of the mixture comprises the following steps: S4-1: coating the membrane solution prepared in S3 onto the substrate, leaving it to stand in a vacuum until a film is formed, peeling it off and drying it; S4-2: The peeled film is worked by spray drying; S4-3: During the drying process, the coating slurry solidifies on the surface of the semi-solid lithium battery separator to form a semi-solid lithium battery separator.
8. The method for preparing a semi-solid lithium battery separator according to claim 7, characterized in that: In S5, the diaphragm detection work includes the following steps: S5-1: Use a sampler to cut 5 samples from the surface of the semi-solid lithium battery separator to be tested; S5-2: Set the test speed, sample name, test times and other parameter information on the intelligent electronic tensile testing machine control software; S5-3: Clamp the sample in a special fixture and install the puncture needle; S5-4: The test starts, and the puncture needle moves to puncture the sample at the set test speed. The equipment displays the force value changes in real time and reports the puncture force value at the end of the test.
9. The method for preparing a semi-solid lithium battery separator according to claim 1, characterized in that: The foamed rubber includes a foaming agent, and the foaming agent is at least one of calcium carbonate, magnesium carbonate and sodium bicarbonate.
10. The method for preparing a semi-solid lithium battery separator according to claim 1, characterized in that: The phenolic foam is prepared by treating polystyrene resin polymerized into beads with pentane under heat and pressure to obtain so-called expandable polystyrene beads.
Citation Information
Patent Citations
A method for preparing a composite high-temperature resistant lithium battery separator material
CN113764820B